Chemical Study of Iraqi Kassub Plant Eryngium creticum Lam and its Geographical Distribution in Diyala Province: Studi Kimiawi Tanaman Kassub Irak Eryngium creticum Lam dan Distribusi Geografisnya di Provinsi Diyala - Nisreen Sabbar Hashim; Kamail Ali Karim; Lubab Ghati Ali; Shireen Mohammed Mahmoods (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: The therapeutic potential of medicinal plants has garnered increasing interest, particularly in relation to their chemical compositions and geographical distributions. Specific Background: This study focuses on Eryngium creticum Lam, an Apiaceae family plant known as Iraqi Kassub, prevalent in the Diyala province of Iraq. Knowledge Gap: Despite its traditional use in treating various ailments, there is a lack of comprehensive chemical analysis and geographical distribution data for this plant. Aims: The objective of this research was to identify the chemical components of Eryngium creticum Lam through GC-MS analysis and to map its geographical distribution within the Diyala province. Results: The chemical study revealed 101 distinct compounds in the alcoholic extract of the plant, highlighting a significant presence of sitosterols and sugars. These compounds are associated with antioxidant properties and therapeutic applications, including the treatment of envenomations, leishmaniasis, and anemia. Novelty: This study is novel in its detailed chemical profiling and geographical mapping of Eryngium creticum Lam, providing new insights into its medicinal value and distribution. Implications: The findings underscore the plant's potential as a therapeutic resource and emphasize the need for further research. Future studies should aim to isolate and characterize bioactive compounds such as phenols and flavonoids and assess their efficacy and safety through in vivo models to validate their therapeutic potential. Highlights: GC-MS identified 101 compounds. Bioactive compounds with therapeutic properties. Mapped geographical distribution in Diyala. Keywords: Eryngium creticum, GC-MS, therapeutic potential, chemical profile, geographical distribution